Leishmania infection in seropositive dogs in the Mucuri Valley Region, Minas Gerais, Brazil (Research, Society and Development, 2022)
Introduction: Canine Visceral Leishmaniasis (CVL) is a severe systemic zoonosis that has the dog as the main reservoir for human disease. As it is a neglected tropical disease, there are gaps in its aspects, especially in regional terms. In this sense, the aim was to evaluate the profile of infected animals and identify the prevalent species in canine infection in the macro-region of Mucuri Valley, Minas Gerais, Brazil, through the polymerase chain reaction (PCR-RFLP-ITS1). Methodology: Cross-sectional observational study carried out between August/2019 and February/2020 at the San Francisco Veterinary Clinic and the Municipal Dog Kennel. Positive animals to the DPP® were selected and biological samples were collected: venous blood (SNAP); ear skin fragment (imprint); and bone marrow aspirate to smear slides, isolation in culture environment, and  molecular diagnosis. All animals underwent clinical examination and data collection: provenance, symptoms, fur, age, sex. Results: In 88 of the 132 samples, the presence of Leishmania’s DNA was detected and in 87.3% the species L. infantum was identified. Of these 88 animals, 69 had symptoms; 45 were males; 73 with short fur. The highest frequency of positive PCR occurred between 2-5 years (55 animals).  91.67% were SNAP test positive. Conclusions: The present study made it possible to understand aspects of CVL in the evaluated samples and to identify the etiological agent most prevalent in the area, allowing the establishment of efficient strategies to control the disease in dogs and to prevent human infection in the region.